Relationship between Occupational Stress and Resilience (Indian Journal of Public Health Research & Development, 2020)
Occupational stress or stress related to workplace refers to stress experienced as a direct result of anindividual’s occupation. or job. Stress completely disturbs the physical, psychological and financial balancesof an employee as well as employers. Due to stress employers cannot expect anticipated outcome fromemployees who are burnt out, drained or stressed, resulting in loss of their drive, determination, clarity andinnovative thinking. Resilience is not just one’s capability to recover from stress, but also ability to adjust inthe face of difficult situations. There is an inverse relationship exists between stress and resilience.
Keywords: Occupational Stress, Employee, Employer, Organization, Resilience, Work load